Angiotensin receptor blockade attenuates cholangiocarcinoma cell growth by inhibiting the oncogenic activity of Yes-associated protein. (10th October 2018) - Saikawa, Soichiro; Kaji, Kosuke; Nishimura, Norihisa; Seki, Kenichiro; Sato, Shinya; Nakanishi, Keisuke; Kitagawa, Koh; Kawaratani, Hideto; Kitade, Mitsuteru; Moriya, Kei; Namisaki, Tadashi; Mitoro, Akira; et al.
Abstract: Cholangiocarcinoma (CCA) is a destructive malignancy with limited responsiveness to conventional chemotherapy. Although angiotensin receptor blockers (ARBs) have gained attention for their potential anticancer activity, little is known about their effects on CCA. The transcriptional co-activator, Yes-associated protein (YAP) is a critical oncogene in several cancers, including CCA. Following recent evidence showing that YAP is regulated by angiotensin II (AT-II), we investigated the effects of an ARB, losartan, on two human CCA cell lines (KKU-M213 and HuCCT-1) with regards to YAP oncogenic regulation. Losartan suppressed AT-II-induced CCA cell proliferation in a dose-dependent manner, induced apoptosis, decreased YAP (Ser127), and downregulated the YAP target genes CTGF, CYR61, ANKRD1, and MFAP5. However, losartan did not affect epithelial–mesenchymal transition, differentiation, or stemness in the CCA cells. Xenograft tumor growth assay showed that oral administration of a low clinical dose of losartan considerably reduced subcutaneous tumor burden and attenuated intratumor vascularization in CCA cell-derived xenograft tumors in BALB/c nude mice. These results indicate that ARB therapy could serve as a potential novel strategy for CCA treatment. Highlights: Angiotensin receptor blocker suppresses human cholangiocarcinoma cell growth. Angiotensin receptor blocker inhibits YAP oncogenic activity. Angiotensin receptor blocker shows anti-angiogenic effect in cholangiocarcinoma.